Better than ploughing - BUCHANAN, J.M. (PSL Quarterly Review, 2013)
The paper is a contribution to a series of recollections and reflections on the professional experiences of distinguished economists which the Banca Nazionale del Lavoro Quarterly Review started in 1979. In it James M. Buchanan offers a retrospective on his life and academic career. JEL: B31